Incidence and risk factors for recurrent spontaneous preterm birth: A retrospective cohort study in Japan. Issue 11 (26th August 2015) - Yamashita, Michiko; Hayashi, Shusaku; Endo, Masayuki; Okuno, Kentaro; Fukui, On; Mimura, Kazuya; Tachibana, Yosuke; Ishii, Keisuke; Mitsuda, Nobuaki; Kimura, Tadashi
Abstract: Aim: The aim of this study was to assess the incidence and risk factors for recurrent spontaneous preterm birth (PTB) in Japan. Material and Methods: A retrospective cohort study was conducted at five tertiary perinatal centers in Osaka, Japan from 2008 through 2012. Perinatal data were collected from medical records of women with a singleton gestation and a previous spontaneous PTB. Exclusion criteria were first‐trimester spontaneous abortion, first antenatal visit beyond 14 weeks of gestation, and previous PTB with medical indications, placenta previa, abruptio placenta, multiple pregnancy, fetal anomaly, and antepartum fetal demise. The associations between recurrent spontaneous PTB and perinatal factors were evaluated by logistic regression analysis. Results: Of 547 women with a previous spontaneous PTB, 89 (16.3%) suffered a recurrent spontaneous PTB. The risk factors for recurrence included multiple previous spontaneous PTB (adjusted odds ratio [aOR]: 2.26; 95% confidence interval [CI]: 1.19–4.30; P  = 0.013), no previous term birth (aOR: 2.08; 95%CI: 1.24–3.49; P  = 0.005), and interpregnancy interval < 12 months (aOR: 2.13; 95%CI: 1.17–3.85; P  = 0.013). Conclusion: Approximately one in six women with a previous spontaneous PTB suffered a recurrent spontaneous PTB. Multiple previous spontaneous PTB, no previous term birth, and short interpregnancy interval were independent risk factors for recurrence.